Triumph From Anguish: The Inspiration of the Special Olympics - Shriver, Timothy (Journal of disability & religion, 2014)
Through violent revolution or quiet changes to laws, societies across the globe are working toward the ideal of equality for all, but this equality is particularly elusive for one segment of the human family—people with intellectual disabilities. In every society on Earth, this population is routinely denied access to health care, education, employment, social contact, and other opportunities that lead to long, fulfilling lives. The Special Olympics movement is waging a dignity revolution worldwide to change this reality though the efforts of hundreds of thousands of volunteers working with more than 4 million athletes. The equality challenge for Special Olympics is unlike that of any other because it does not rest on the ideal of achieving sameness but rather on the opposite ideal of welcoming difference. This will require not just the addition of services for “them” but an attitude change for all of “us.” When international bodies and policymakers meet, they will need to include people with intellectual disabilities at the table. When metrics are set, leaders will need unequivocal targets to reach. When censuses and other measurements are made, they will need to include this population and ensure they are no longer hidden. Finally, people the world over will need to adopt an open mind and an unleashed heart. Then, we can declare victory in the dignity revolution for people with intellectual disabilities.